Legal Policy Regarding Criminal Actions of Narcotics Trafficking Involving Children - Dani Harianto (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
Distribution case narcotics involved child the more increase along development technology and convenience access facility general. Involvement children in narcotics distribution is problem seriously threatening generation successor nation. The perpetrator's son is often entangled in the network distribution adult narcotics so that potential become victims of exploitation. Although accordingly, the Law Number 35 of 2009 concerning Narcotics No differentiate in a way special age perpetrator dealer narcotics. Criminal law approach should be more directed at effort rehabilitation child than condemnation, remembering child perpetrator tend become a victim. Therefore, that country through government and society is obliged to protect children involved in the act of criminal narcotics distribution.